Un exemple de genre fluide dans la nécropole du Céramique ? - Isabelle Algrain (Frontière·s)
The question of identifying a third gender or gender fluidity in archaeological contexts has already been explored for many geographical areas and time periods. However, scholars studying Classical Greece, and Athens especially, have not so far taken up this subject. Yet, even if classical Athens seems to portray a strictly binary society, some deities and individuals have the distinctive feature of blurring the gender boundaries. This is particularly the case with actors, and this paper will focus on the burial of the actor Makareus, discovered in the Kerameikos Necropolis and dated to the 4th century BC. On the basis of the material from this grave, and considering the data related to actors in the ancient sources, we will reconsider the idea proposed by several researchers that the actors belonged to the female gender, before suggesting an alternative interpretation, based on gender fluidity.